Neighborhood racial composition and poverty in association with pre-pregnancy weight and gestational weight gain - Dara D. Mendez; Roland J. Thorpe; Ndidi Amutah; Esa M. Davis; Renee E. Walker; Theresa Chapple-McGruder; Lisa Bodnar (Elsevier, 2016)
Background: Studies of neighborhood racial composition or neighborhood poverty in association with pregnancy-related weight are limited. Prior studies of neighborhood racial density and poverty has been in association with adverse birth outcomes and suggest that neighborhoods with high rates of poverty and racial composition of black residents are typically segregated and systematically isolated from opportunities and resources. These neighborhood factors may help explain the racial disparities in pre-pregnancy weight and inadequate weight gain. This study examined whether neighborhood racial composition and neighborhood poverty was associated with weight before pregnancy and weight gain during pregnancy and if this association differed by race. Methods: We used vital birth records of singleton births of 73,061 non-Hispanic black and white women in Allegheny County, PA (2003-2010). Maternal race and ethnicity, pre-pregnancy body-mass-index (BMI), gestational weight gain and other individual-level characteristics were derived from vital birth record data, and measures of neighborhood racial composition (percentage of black residents in the neighborhood) and poverty (percentage of households in the neighborhood below the federal poverty) were derived using US Census data. Multilevel log binomial regression models were performed to estimate neighborhood racial composition and poverty in association with pre-pregnancy weight (i.e., overweight/obese) and gestational weight gain (i.e., inadequate and excessive). Results: Black women as compared to white women were more likely to be overweight/obese before pregnancy and to have inadequate gestational weight gain (53.6% vs. 38.8%; 22.5% vs. 14.75 respectively). Black women living in predominately black neighborhoods were slightly more likely to be obese prior to pregnancy compared to black women living in predominately white neighborhoods (PR 1.10; 95% CI: 1.03, 1.16). Black and white women living in high poverty areas compared with women living in lower poverty areas were more likely to be obese prior to pregnancy; while only white women living in high poverty areas compared to low poverty areas were more likely gain an inadequate amount of weight during pregnancy. Conclusions: Neighborhood racial composition and poverty may be important in understanding racial differences in weight among childbearing women. Keywords: Neighborhood, Race, Poverty, Pregnancy, Weight